Colloid Oncotic Pressure in Children with Nephrotic Syndrome - Taralan Tambunan; H. Alatas; I. G. N. Wila Wirya; S. Harmanses; I. Chair; R. Simanjuntak (Paediatrica Indonesiana, 1988)
To evaluate the correlation between plasma protein concentration and colloid oncotic pressure (COP) and their influence on clinical symptom of edema, we studied 30 children with nephrotic syndrome (NS). Total plasma protein concentration (TP), albumm, globulin and COP were measured in all patients in edema forming state (EF) and m steady state phase (SS), except for COP, only 16 samples in SS phase. COP TP plasma albumin and globulin contents in EF group were 8. 7 ± 2. 7 mmHg, 4.07 '± 0.68 g/dl; 2.57 ± 0.50 g/dl and 1.51 ± 0.32 g/dl, respectively. In SS group these figures rose significantly to 16.7 ± 3.9 mmHg for COP; 5. 70 ± 0.99 g/dl for TP; 3.46 ± 0.52 g!dl and 2.06 ± 0.56 g/dl for plasma albumin and globulin, respectively. We also found the high correlation both between COP and albumin content (r= +0.58; p < 0.01) and between COP and TP (r= +0.54; P < 0.01) . A strong negative correlation was also found between COP and the degree of edema (r = _ 0.55; p <0.01). On the other hand a very low grade correlation was noticed between plasma albumin content and the degree of edema (r= - 0.26; P < 0.05) and no correlation at all was found between edema and TP (r= - 0.19; P > 0.05). We conclude that COP has the highest correlation with plasma protein concentration and the degree of edema, and can be used as a diagnostic tool. It is even more sensitive and simple compared with the TP or albumin content determination.